Association and Implications of Blood and Plaque n-3 Polyunsaturated Fatty Acid Composition in Patients Treated with Oral Eicosapentaenoic Acid before Carotid Endarterectomy - Ishikawa, Tatsuya; Yamaguchi, Koji; Funatsu, Takayuki; Okada, Yoshikazu; Kawamata, Takakazu (International Journal of Angiology, 2021)
Long-chain n-3 polyunsaturated fatty acids (PUFA), especially eicosapentaenoic acid (EPA), have been shown to prevent atherosclerosis-related cardiovascular disease, including stroke. Recently, the ratio of serum EPA to arachidonic acid (AA; EPA/AA ratio) has been reported to be a biomarker to prevent cardiovascular disease. In this study, we evaluate whether the serum EPA/AA ratio would be a useful biomarker for determining the efficacy of orally administered EPA in preventing stroke by investigating tissue and serum EPA/AA ratios, serum inflammatory markers, and carotid artery intimamedia thickness (IMT). Patients with dyslipidemia, as the primary illness scheduled for carotid endarterectomy (CEA), were included and randomly assigned to the EPA group (EPA: 1,800 mg/day plus statin; 10 patients) or non-EPA group (statin only; 15 patients). PUFA fraction was evaluated in the tissue (post-CEA) and serum (pre-CEA and 6 months thereafter). As for the tissue PUFA fraction in the plaque, the EPA group had a significantly higher EPA/AA ratio (EPA group, 0.46; non-EPA group, 0.28; p = 0.01). At 6 months postoperatively, the EPA group had a significantly higher serum EPA/AA ratio (baseline, 0.83; follow-up, 1.60; p = 0.05). No significant differences were found for inflammatory markers and IMT. Both serum and tissue EPA/AA ratios were higher in patients treated with oral EPA. Serum EPA/AA ratio might be a useful biomarker for the efficacy of orally administered EPA.
Keywords: eicosapentaenoic acid; carotid endarterectomy; fatty acid; eicosapentaenoic acid/arachidonic acid ratio; atherosclerosis; biomarker; carotid artery stenosis